The Influence of Local Pamidronate Application on Alveolar Dimensional Preservation after Tooth Extraction—An Animal Experimental Study - Frederic Kauffmann (International Journal of Molecular Sciences, 2020)
The aim of this randomized, controlled animal exploratory trial was to investigate the influence of local application of aminobisphosphonate pamidronate during the socket preservation procedure. Mandibular premolars were extracted in five Göttingen minipigs. Two animals underwent socket preservation using BEGO OSS (n = 8 sockets) and three animals using BEGO OSS + Pamifos (15 mg) (n = 12 sockets). After jaw impression, cast models (baseline, eight weeks postoperative) were digitized using an inLab X5 scanner (Dentsply Sirona) and the generated STL data were superimposed and analyzed with GOM Inspect 2018 (GOM, Braunschweig). After 16 weeks, the lower jaws were prepared and examined using standard histological methods. In the test group (BEGO OSS + pamidronate), buccooral dimensional loss was significantly lower, both vestibulary (0.80 ± 0.57 mm vs. 1.92 ± 0.63 mm; p = 0.00298) and lingually (1.36 ± 0.58 mm vs. 2.56 ± 0.65 mm; p = 0.00104) compared with the control group (BEGO OSS). The test group showed a significant difference between vestibular and lingual dimensional loss (p = 0.04036). Histology showed cortical and cancellous bone in the alveolar sockets without signs of local inflammation. Adjuvant application of pamidronate during socket preservation reduces alveolar dimensional loss significantly. Further investigations with regard to dose–response relationships, volume effects, side effects, and a verification of the suitability in combination with other bone substitute materials (BSMs) are necessary.